Tell them we are rising a memoir of faith in education - Hayre, Ruth Wright 1910- (Wiley, 1997)
Ruth Wright Hayre grew up in a close, genteel family that had prized learning since the days of the Civil War. At age ten, her grandfather, Richard Robert Wright, led by his remarkable mother, marched 200 miles to attend a school for emancipated slaves in a discarded railroad boxcar in Atlanta.